White-Simulation - Abdulrahman Shashtari; Mahmoud Barmawi (My University, 2025)
Interactive tools play an important role in modern education, creating a better learning environment by making complex concepts more intelligible and accessible. Simulations offer effective ways of visualization and experimentation. This allows students to understand complex abstract ideas through direct handling. This has been particularly more useful in subjects like physics, mathematics, and computer science, where the understanding of a theoretical concept has to be made clear with dynamic presentations and experimentation. To this end, we have developed a desktop application that integrates interactive simulations, notetaking, and collaboration into one platform. This application will include a variety of simulations, including pendulum motion, additive wave functions, gravitational interactions, algorithm visualizations such as bubble sort. These let users play with parameters, observe results, and intuitively understand how things work. One of the unique selling points of our application is the inclusion of a digital whiteboard in addition to the simulations. The whiteboard is useful for freehand drawing, annotation, and explanation. One can place the simulations on the whiteboard, explain with notes, and connect visuals for better understanding. This integration enables active learning wherein simulations and notes coexist in one single workspace, promoting deeper and cohesive learning. It further allows saving and sharing of whiteboard notes, enabling the user to share in collaboration and community through shared knowledge and insight. Sharing annotated simulations and notes makes the platform a very useful tool for educators and students alike, promoting collaborative learning and discussion. From a technical perspective, the application was developed with several modern technologies. It used Electron.js to build the desktop interface for cross-platform use and Node.js, with Express.js, for server-side operations. The application makes use of PostgreSQL as a database to securely store user data and notes shared by them. Our aim is to provide a comprehensive tool that empowers learners for exploration, visualization, and sharing of knowledge, thus making education more interactive and joyful. With this application, we are trying to fill the gap in theoretical knowledge and practical understanding through an appealing collaborative learning environment. 4